Predictors of expressed, felt, and normative needs for informal caregiver counseling: Domestic care for people aged 65+ years - Scheuermann, Julia-Sophia; Grässel, Elmar; Pendergrass, Anna (Zeitschrift für Gerontologie und Geriatrie, 2022)
Background: Informal caregivers (CGs) often fail to recognize or express a need for informal caregiver counseling (ICC) but ICC is an essential but relatively rarely used support service for CGs. Objective: Our aim is to identify predictors of CGs’ need for ICC. Stirling et al.’s need model, which includes three needs (expressed, felt, and normative), serves as a theoretical basis. Material and methods: Analyses are based on cross-sectional data (n = 958) from the “Benefits of being a caregiver” study. Predictors of the need to use ICC were analyzed with binary logistic regression. A sensitivity analysis using multiple linear regression was performed for the metric value of normative needs. Results: We found that 6.8% of CGs currently or have recently used ICC. This expressed need was related to higher education and higher effort in instrumental activities; 24.1% of CGs reported an intention to use ICC in the future. This felt need was related to male gender, lower care level, more problem-focused coping, and a desire for more informal help. Objective need for ICC (normative need), which was related to a higher burden of care, less experienced benefits, and negative relationship quality, was reported by 21.4% of CGs. According to a sensitivity analysis, higher education, a desire for informal help, and living in separate households also predicted a normative need for counseling. Discussion: Current utilization is significantly lower than the subjectively perceived and objectively existing need for ICC. The identified predictors provide initial strategies for motivating more CGs to use ICC.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Home care; Informal caregiver counseling; Informal caregivers; Needs; Utilization